Settled and unsettling: design and flows of affect in a hospital waiting area. Issue 1 (2nd January 2020) - Fadyl, Joanna K; Cunningham, Helen; Nakarada-Kordic, Ivana; Reay, Stephen; Waters, Tineke; Waterworth, Kate; Gibson, Barbara E
Abstract: Waiting in healthcare environments is common, and the design of waiting areas can profoundly participate in that experience. This paper describes a study drawing on Deleuze and Guattari's notions of 'affect' and 'assemblage' to investigate a hospital waiting area: exploring how the area currently participates in the generation of affect and how it could better support human 'becomings'. Analysis of generated observational data identified 'affective assemblages' that produced recurring affects encountered in the waiting area, here labelled crisis, workaday world, and episodic home . Thinking in terms of assemblages forced the analysis to direct attention to a wide variety of 'elements' that participate in the production of spaces and the affects encountered in this type of waiting area. These included bodies, objects, time, sounds and smells, social conventions and cultural norms. It also allowed a discussion of the effects of inter-action between affects – identifying aspects that, while initially interpreted as 'problems', may also be producing opportunities important to the functioning of the space. The paper concludes with a discussion of the implications for design, suggesting that analyses of 'affective assemblages' produces potentially fruitful 'lines of flight' for generating questions and possible responses that challenge notions of simply 'solving design problems'.